Self-powered DNA nanomachines for fluorescence detection of lead - Li, Xiang-Ling; Jiang, Han; Zhao, Lei; Song, Tian shun; Xie, Jing jing (Mikrochimica acta (1966), 2023)
A versatile DNA nanomachine detection system has been developed via the combination of DNAzyme with catalytic hairpin assembly (CHA) technology for achieving accurate and sensitive detection of lead ions (Pb 2+ ). In the presence of target Pb 2+ , capture DNA nanomachine formed by AuNP and DNAzyme recognized and reacted with Pb 2+ , which yielded an “active” DNAzyme, that induced the cleavage of substrate strand, and then released the initiator DNA (TT) for CHA. With the help of the initiator DNA TT, self-powered CHA was activated to achieve the signal amplification reaction in the detection of DNA nanomachine. Meanwhile, the initiator DNA TT was released and hybridized with the other H1 strand to initiate another CHA, replacement, and turnovers, producing enhanced fluorescence signal of fluorophore FAM (excitation 490 nm/emission 520 nm) for sensitive determination of Pb 2+ . Under the optimized conditions, the DNA nanomachine detection system revealed high selectivity toward Pb 2+ in the concentration range 50–600 pM, with the limit of detection (LOD) of 31 pM. Recovery tests demonstrated that the DNA nanomachine detection system has excellent detection capability in real samples. Therefore, the proposed strategy can be extended and act as a basic platform for highly accurate and sensitive detection of various heavy metal ions. Graphical Abstract